Thoracoscopic Approach for Congenital Diaphragmatic Hernia: A Useful Tool in Diagnosis and Treatment of Unexpected Associated Lung Lesion - Mario Lima; Michela Maffi; Tommaso Gargano; Giovanni Ruggeri; Michele Libri; Francesca Destro (Georg Thieme Verlag KG, 2016)
Abstract We report the case of a neonate affected by prenatally diagnosed congenital diaphragmatic hernia (CDH), treated by thoracoscopy. During the procedure, we detected an associated extralobar pulmonary sequestration (EPS), which was preoperatively undiagnosed, and we removed it. EPS has been shown to be associated with CDH in up to 15 to 40% of cases. A possible explanation hypothesized is that pulmonary sequestration, which develops at 4 to 5 weeks of gestation, can disturb the fusion of the diaphragm and closure of the pleuroperitoneal canal. The thoracoscopic approach permitted us to identify the thoracic EPS that probably would have been otherwise missed.